Relationship between Electronic Banking and Customer Satisfaction: Evidence from Enugu, Nigeria - Ejike Miracle Okechukwu; Nwosu Kanayo Chike; Nuel-Okoli Chinenye Maureen (Innovation Business Management and Accounting Journal, 2025)
Extant literature has shown conflicting results on the relationship between e-banking and bank customer satisfaction. Moreover, this research area has scanty empirical evidence in Nigeria. As a result, this study examined the relationship between e-banking and customer satisfaction in Enugu, Nigeria. The research was anchored on Davis’ (1989) technology acceptance model. The study population comprises 1,004,132 adult bank customers. A sample of 400 customers was determined using Yamane’s formula. The survey utilized convenience sampling to select participants who had used the e-banking tools. The research data were collected and analyzed using a structured questionnaire and Pearson Product-moment Correlation technique. The survey determined a positive correlation among Internet banking, ATM, POS, mobile banking, and customer satisfaction. The management of banks was advised to conduct period security checks on the firm’s websites; monitor and update ATMs at regular intervals; standardize POS service operations and charges for banks and independent operators; and deploy user-friendly mobile Apps for effective service delivery.